Exploring the Conserved Role of MANF in the Unfolded Protein Response in Drosophila melanogaster. - Riitta Lindström; Päivi Lindholm; Jukka Kallijärvi; Mari Palgi; Mart Saarma; Tapio I Heino (PLoS ONE)
Disturbances in the homeostasis of endoplasmic reticulum (ER) referred to as ER stress is involved in a variety of human diseases. ER stress activates unfolded protein response (UPR), a cellular mechanism the purpose of which is to restore ER homeostasis. Previous studies show that Mesencephalic Astrocyte-derived Neurotrophic Factor (MANF) is an important novel component in the regulation of UPR. In vertebrates, MANF is upregulated by ER stress and protects cells against ER stress-induced cell death. Biochemical studies have revealed an interaction between mammalian MANF and GRP78, the major ER chaperone promoting protein folding. In this study we discovered that the upregulation of MANF expression in response to drug-induced ER stress is conserved between Drosophila and mammals. Additionally, by using a genetic in vivo approach we found genetic interactions between Drosophila Manf and genes encoding for Drosophila homologues of GRP78, PERK and XBP1, the key components of UPR. Our data suggest a role for Manf in the regulation of Drosophila UPR.